2022
DOI: 10.1101/2022.10.04.510633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

142 telomere-to-telomere assemblies reveal the genome structural landscape inSaccharomyces cerevisiae

Abstract: As population genomics is transitioning from single reference genomes to pangenomes, major improvements in terms of genome contiguity, phylogenetic sampling, haplotype phasing and structural variant (SV) calling are required. Here, we generated the Saccharomyces cerevisiae Reference Assembly Panel (ScRAP) comprising 142 reference-quality genomes from strains of various geographic and ecological origins that faithfully represent the genomic diversity and complexity of the species. The ca. 4,800 independent SVs … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 119 publications
2
21
0
Order By: Relevance
“…While traditionally considered suboptimal for the imaging of intracellular features, super‐resolution techniques were recently developed (Chen et al, 2021; Hinterndorfer et al, 2022; Korovesi et al, 2022), and used (Dey et al, 2020) in yeast to study cellular processes at higher resolution, and new tools have been provided for the imaging of several subcellular structures (Akhuli et al, 2022; Zhu et al, 2019). A large number of telomere‐to‐telomere assemblies recently revealed the landscape of structural variants of S. cerevisiae natural isolates (O'Donnell et al, 2022). Finally, synthetic biology approaches such as The Synthetic Yeast Genome Project (S. M. Richardson et al, 2017) continue to provide novel tools to generate synthetic cellular conditions.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…While traditionally considered suboptimal for the imaging of intracellular features, super‐resolution techniques were recently developed (Chen et al, 2021; Hinterndorfer et al, 2022; Korovesi et al, 2022), and used (Dey et al, 2020) in yeast to study cellular processes at higher resolution, and new tools have been provided for the imaging of several subcellular structures (Akhuli et al, 2022; Zhu et al, 2019). A large number of telomere‐to‐telomere assemblies recently revealed the landscape of structural variants of S. cerevisiae natural isolates (O'Donnell et al, 2022). Finally, synthetic biology approaches such as The Synthetic Yeast Genome Project (S. M. Richardson et al, 2017) continue to provide novel tools to generate synthetic cellular conditions.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…With the SGDref as the reference genome, we incrementally added those 162 ScRAP assemblies into the graph according to their phylogenetic distances to SGDref. The phylogenetic distances employed here were extracted from the phylogenetic tree of these 163 input genomes built upon their concatenated 1-to-1 orthologous gene matrix (See [16] for details). Regarding the haplotype tag, for the yeast reference pangenome graph, we used “HP0” to denote haplotypes of haploid or homozygous diploid strains, while using “collapsed”, “HP1”, and “HP2” to denote collapsed, or the two phased haplotypes of heterozygous diploid strains.…”
Section: Methodsmentioning
confidence: 99%
“…To demonstrate the application of VRPG in real world examples, we set up a demonstration website (https://www.evomicslab.org/app/vrpg/) to visualize reference pangenome graphs derived from 143 yeast and 90 human genome assemblies respectively. The human reference pangenome graph is a public dataset, whereas the yeast reference pangenome graph is built based on the Saccharomyces cerevisiae reference assembly panel (ScRAP) that we recently constructed (O’Donnell et al ., 2022). Both graphs were constructed by Minigraph (Li et al ., 2020) via a standard reference pangenome graph building protocol (Supplementary Note).…”
Section: Application Demonstrationmentioning
confidence: 99%
“…While producing collapsed assemblies for haploid or predominantly homozygous genomes is relatively straightforward, complex heterozygous genomes are much more difficult to characterize at the haplotype level. Recent studies demonstrated the feasibility of the approach (Heasley and Argueso, 2022; O’Donnell et al, 2023), but the task of resolving hybrid genomes across a wide range of parental divergence under a unified framework remains challenging. Here, we employ a phasing and assembly approach using long reads to resolve hybrid MA lines genomes.…”
Section: Introductionmentioning
confidence: 99%